Exact tests using binary data in adaptive two or multi-stage designs. (August 2020) - Yin, Huan; Wang, Weizhen; Zhang, Zhongzhan
When establishing an effective treatment with binary data in a two-stage design, one-sided tests for a proportion p are employed. Researchers use the parameter configuration at the boundary of the null hypothesis space to determine a rejection region and an optimal design. However, it is unclear whether the (maximum) Type I error rate is achieved at the boundary especially when the sample size in stage 2 varies. In this paper, we first prove that this is true for a large family of tests in adaptive two-stage designs by showing that any test in the family has a nondecreasing power in p and then derive optimal designs. Second, similar results are established for m -stage designs with m  >   2. Supplementary materials for this article are available online.